(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Atrial fibrillation is one of the most common cardiac arrhythmias, causing dangerous complications. This article reviews the main risk factors associated with the development of atrial fibrillation, including hypertension, diabetes, smoking, obesity, and metabolic syndrome. Analysis of modifiable risk factors can contribute to the development of preventive measures aimed at reducing the incidence of this arrhythmia.